Študijsko gradivo pri predmetu Sistem sodnega varstva v EU: Zbirka vaj - Hojnik, Janja; Weingerl, Petra; Šuta, Živa (University of Maribor Press, 2023)
Study Material for the Course The EU Judicial System: Collection of Exercises. This study material is intended for second cycle students at the Faculty of Law, University of Maribor, enrolled in the course The EU Judicial System. It gives an overview of proceedings before the Court of Justice of the European Union (CJEU) and categorizes direct actions as those against Member States and those against EU institutions, followed by practice exercises on the preliminary ruling procedure, which is the only representative of indirect proceedings. Two chapters at the beginning of the material are intended to refresh knowledge of the fundamentals of EU law, with a focus on the relationship between EU law and national law, as well as the role of the CJEU in the EU institutional architecture. The material assesses and tests student’s knowledge through theoretical questions, points for discussion and practical examples.